Religion, Identity and Power Turkey and the Balkans in the Twenty-First Century - Öztürk, Ahmet Erdi (Edinburgh Studies on Modern Turkey, 2021)
This book examines Turkey's ethno-religious activism and power-related political strategies in the Balkans between 2002 and 2020, the period under the rule of the Justice and Development Party (AKP), to determine the scopes of its activities in the region.